Supporting sacrifice or condemning belief: consumer reactions to Nike's advertising campaign featuring Colin Kaepernick. (14th May 2021) - Asada, Akira; Sanderson, Jimmy
The purpose of the current study was to explore the key personal and emotional factors related to consumers' reactions to Nike's 'Believe in Something' advertising featuring Colin Kaepernick. The results of a survey with 254 US consumers indicated that: a) dominance and egalitarianism had positive relationships with purchase intention, whereas uncritical patriotism had a negative relationship; b) anger, gratitude, and pride mediated the effects of dominance, egalitarianism, uncritical patriotism on purchase intention, whereas contempt did not show a mediation effect. The present study contributes to the sport marketing literature as one of the first studies to examine the effects of controversial advertising on sports consumers' emotions and behaviours. The results also provide unique insights for sports brands to develop effective promotion strategies.